Innovation as a strategy for economic development - Araujo, Pedro Quaresma de (Faculdade de Ciências e Letras - Unesp - Araraquara., 2020)
From a structuralist perspective, the incorporation of technical progress is a key element for the promotion of development for which the State plays a preponderant strategic role. For Schumpeter, in his celebrated formulation of “creative destruction”, we can say that innovation is the driving force behind capitalism, constituting a continuous process, cumulative, dependent on financing, and a key element for the companies’ competitive strategy and the national economic growth. That is, even in more developed economic stages, innovation is what ensures the competitiveness of companies in the market, thus justifying the contribution of public resources dedicated to this end. In this sense, the aim of this article is to present a brief international review of public support instruments for innovation, highlighting the performance of development banks, drawing on the example of Germany, China, Japan, Korea and in the case of the USA. federal agencies in supporting companies in that country.